IMPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR TRADISIONAL DI KABUPATEN BANTUL - , Abdul Kadir Shofari, SSTP, Dr. Ely Susanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
As part of efforts to protect the local community economy, the Local Government of Bantul creates new policies in managing traditional markets. This policy is in the form of physical reconstruction and trader empowerment through providing assistance revolving funds. As a new policy, it is aimed to create a good and fair business environment between the traditional market and modern market. This research aimed to know how the implementation of management policies in traditional markets is in Bantul and factors that affect the implementation of these policies, especially in the three traditional markets namely Niten Market, Imogiri Market, and Piyungan Market. These market are the pilot project from the traditional market management policies in Bantul and the policy has run for two years. This study used qualitative methods and data was collected by in-depth interviews and observation. The research found that the implementation of the management of traditional markets in Bantul was constrained by several factors, such as content and implementer of policy. The contents of the policy were incomplete, lack of professionalism and capability of implementing. Such lack of facilities and infrastructure policies lead to the poor achievement of outcomes. Meanwhile, when viewed from a relatively homogeneous target groups, the result provided convenience in implementing the policy. This study recommends that the government should evaluate the policy before being implemented to the next target groups. In addition, other policies need to be done to support the traditional market management policies in Bantul.